2019
DOI: 10.2144/btn-2018-0162
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Injections as an Alternative Method for Micro-CT Contrast Enhanced Detection of Murine Liver Tumors

Abstract: Micro-computed tomography (micro-CT) coupled with tissue, or vascular, specific contrast agent has emerged as a powerful tool for detecting and monitoring tumor growth in the liver of murine animals. Intravenous injections of contrast agents can be technically challenging and lead to errors that can considerably influence the outcome of a preclinical study, prompting an alternative method. Here we assessed the effectiveness of intraperitoneal injections of polyiodinated triglycerides emulsions (Fenestra LC) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, long-term follow-up was not performed, unlike in our study. Considering these previous successful longitudinal imaging studies and the results of our own study, 2,24 -26 longitudinal imaging using nanoparticle contrast agents and microCT may offer an effective tool for the follow-up of liver cancer mouse models.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, long-term follow-up was not performed, unlike in our study. Considering these previous successful longitudinal imaging studies and the results of our own study, 2,24 -26 longitudinal imaging using nanoparticle contrast agents and microCT may offer an effective tool for the follow-up of liver cancer mouse models.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, the smallest liver cancer nodule that could be identified on microCT imaging was 0.60 mm, as compared with the minimum discernible size of 0.30 mm in a previous study. 2 Recently, there was a report of an injection of hepatocellular-specific contrast agent (Fenestra LC, MediLumine Inc., Montreal, Canada) into the abdominal cavity to obtain a contrast-enhanced image of the hepatic parenchyma without requiring initial injection through the lateral tail vein 24 ; however, serial imaging required multiple injections of contrast media into the abdominal cavity. Furthermore, images need to be obtained 16 h after contrast agent injection to obtain the best image, and the contrast enhancement intensity was lower than that obtained with the ExiTron nano 12000 used in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…15 With tissue or vascular specific contrast agents, CT has become a powerful tool to monitor tumor growth in animal livers. 16 CECT is able to grasp the "fast-in and out" feature of HCC lesions and exhibit the blood flow in the tumor. 17 A normal liver derives 80% of its blood from the portal vein and the other 20% from the hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
“…Among those modalities, X-ray micro-CT has gained significant traction for several reasons, including its noninvasive 3D imaging capability, isotropic spatial resolution (∼ 10 – 100 μm), good balance between resolution and field of view, fast speed, easy processing, and relatively low cost compared to MRI (Clark and Badea 2021). Since tumors generally have similar density to their surrounding tissues, contrast material is needed for improved tumor visibility when using micro-CT. For example, Fenestra LC is one of the most used nanoparticle (NP)-based contrast agents for liver and spleen micro-CT imaging (Bakan et al 2000, Sweeney et al 2019) as they can be taken up by phagocytic cells and accumulate in functioning liver or spleen regions. Several NP-based blood stream contrast agents have been used to monitor the development of liver and spleen tumors in a longitudinal manner (Almajdub et al 2007, Kim et al 2008, Boll et al 2011, Sweeney et al 2019, Cassol et al 2019, Liu et al 2019), via volume extraction (Cassol et al 2019), and vascularity (Sulheim et al 2018) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Since tumors generally have similar density to their surrounding tissues, contrast material is needed for improved tumor visibility when using micro-CT. For example, Fenestra LC is one of the most used nanoparticle (NP)-based contrast agents for liver and spleen micro-CT imaging (Bakan et al 2000, Sweeney et al 2019) as they can be taken up by phagocytic cells and accumulate in functioning liver or spleen regions. Several NP-based blood stream contrast agents have been used to monitor the development of liver and spleen tumors in a longitudinal manner (Almajdub et al 2007, Kim et al 2008, Boll et al 2011, Sweeney et al 2019, Cassol et al 2019, Liu et al 2019), via volume extraction (Cassol et al 2019), and vascularity (Sulheim et al 2018) measurements. However, compared with liver/spleen tumors, breast tumor imaging is more challenging, since NPs can accumulate in liver and spleen tissues, forming a negative contrast for tumors and enabling a clear discrimination between tumors and surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%